Efforts of Islamic Religion Teachers in Overcoming Difficulties in Quran Reading Among 12th Grade Students at State Senior High School 12 Medan - Syaharani, Liza; Ismaraidha, Ismaraidha (Universitas Syiah Kuala, 2025)
Teachers' efforts in Islamic education are by educating, educating is a big task for a teacher, educating is partly in the form of teaching students, there is also in the form of giving encouragement to students, giving good examples, praising, and getting used to it. There are many obstacles during learning, for example, the lack of Islamic Religious Education learning hours in schools, lack of discipline towards students, environmental factors that make them lazy to learn to read the Koran at this age, there are also family factors that do not encourage their children to learn. reading the Al-Quran every day, the efforts of all teachers are expected to be able to overcome students who cannot read the Al-Quran and make it a special goal for all students. This research aims to examine PAI Teachers' Efforts in Overcoming Difficulties in Reading the Al-Quran for Class XII Students at SMA Negeri 12 Medan. This research began with the large number of students who had difficulty reading the Al-Quran to students. This research uses qualitative methods, with a case study type of research. Data collection techniques through interviews, observation and documentation. The data analysis technique uses the Miles and Huberman model with stages of data reduction, data presentation, and drawing conclusions